PREPARATION AND IN VITRO EVALUATION OF NAPROXEN AS A pH SENSITIVE OCULAR IN-SITU GEL - DAWOOD, BAYDAA Y.; KASSAB, HANAN J. (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study was to prepare and evaluate a pH sensitive ocular in-situ gel of Naproxen, to increase the ocular residence time. Methods: pH sensitive in situ gel formulations were prepared using different concentrations of Carbomer CB [0.5%, 0.6%, 0.7%] in combination with hydroxypropyl methylcellulose HPMC K40 [0.75%, 1%, 1.5%] or HPMC K100 [0.5%, 0.75%, 1%, 1.5%]. The prepared in situ gels were evaluated for appearance, pH, gelling capacity [sol-to-gel transition/in vitro], tonicity, viscosity, in vitro release studies, release kinetic analysis, and the selected formulas were subjected to rheological studies, and the finally selected formula was subjected to drug content, FT-IR studies, and ocular irritancy tests. Results: Increasing the concentration of the carbomer polymer improved the gelling capacity and gelation time, also the higher the viscosity and concentration of the hydrophilic HPMC polymer, the higher the viscosity of the formula, which affected the release, gelation capacity and time. The overall results showed that formula F10 [CB 0.7%, HPMC K100 0.75%] exhibited excellent pH-triggered in-situ gelation time, sustained the release of naproxen for 3 h’ time with a release rate of more than 90%. Conclusion: Ocular in situ gel of naproxen offers a potential dosage form to increase the residence time in the ocular cul de sac, decreasing the drug drainage, and increasing the effectiveness of the drug.